Analysis of Mathematical Critical Thinking Ability viewed from Habits of Mind - Nurmaliza, Nurmaliza; Dahlia, Agus; Nufus, Hayatun; Nurdin, Erdawati (Jurnal Pendidikan MIPA, 2022)
This study aims to describe mathematical critical thinking ability viewed from habits of mind. Type of research was qualitative with case study method. Research subjects were 28 students of class XI SMAN 1 Tembilahan Hulu. Data collection technique used mathematical critical thinking ability test, habits of mind questionnaire and interview guidelines. Data analysis technique was carried out stages which included data reduction, data presentation, and drawing conclusions. Based on results of the study, it shows that students with high habits of mind have high critical thinking skills which are characterized by students being able to master three critical thinking indicators. Students with moderate habits of mind have abilities in moderately critical category, which is characterized by students being able to master two critical thinking indicators, while students with low habits of mind have abilities in moderately critical category where students being able to master one indicator of critical thinking skills. Keywords: critical thinking ability, habits of mind, mathematic, analysis. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp904-917